2013
DOI: 10.1104/pp.113.225649
|View full text |Cite
|
Sign up to set email alerts
|

GDSL LIPASE1 Modulates Plant Immunity through Feedback Regulation of Ethylene Signaling  

Abstract: Ethylene is a key signal in the regulation of plant defense responses. It is required for the expression and function of GDSL LIPASE1 (GLIP1) in Arabidopsis (Arabidopsis thaliana), which plays an important role in plant immunity. Here, we explore molecular mechanisms underlying the relationship between GLIP1 and ethylene signaling by an epistatic analysis of ethylene response mutants and GLIP1-overexpressing (35S:GLIP1) plants. We show that GLIP1 expression is regulated by ethylene signaling components and, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 72 publications
5
68
0
Order By: Relevance
“…It was reported recently that EIN3 is greatly elevated in expression and transcriptional activity during leaf senescence and accelerates senescence by repressing miR164 through direct binding to the miR164 promoter (Li et al ., ). We previously demonstrated that GDSL lipase 1 (GLIP1) promotes EIN3 degradation, thereby downregulating EIN3 (Kim et al ., ). The decrease in miR164 levels in the glip1‐1 mutant, as shown in microarray analysis of miRNAs and qRT‐PCR expression analysis, may be explained by GLIP1‐mediated EIN3 downregulation (Kim et al ., ) and EIN3‐mediated miR164 downregulation (Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was reported recently that EIN3 is greatly elevated in expression and transcriptional activity during leaf senescence and accelerates senescence by repressing miR164 through direct binding to the miR164 promoter (Li et al ., ). We previously demonstrated that GDSL lipase 1 (GLIP1) promotes EIN3 degradation, thereby downregulating EIN3 (Kim et al ., ). The decrease in miR164 levels in the glip1‐1 mutant, as shown in microarray analysis of miRNAs and qRT‐PCR expression analysis, may be explained by GLIP1‐mediated EIN3 downregulation (Kim et al ., ) and EIN3‐mediated miR164 downregulation (Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We previously demonstrated that GDSL lipase 1 (GLIP1) promotes EIN3 degradation, thereby downregulating EIN3 (Kim et al ., ). The decrease in miR164 levels in the glip1‐1 mutant, as shown in microarray analysis of miRNAs and qRT‐PCR expression analysis, may be explained by GLIP1‐mediated EIN3 downregulation (Kim et al ., ) and EIN3‐mediated miR164 downregulation (Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Total and free SA were quantified as previously described (Kim et al , ; Quentin et al , ). Leaf samples (150 mg), together with o ‐anisic acid (50 ng) as an internal standard, were ground in liquid nitrogen and extracted with 90% methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Genes belonging to PF00067 were up-regulated in all pathosystems and this Pfam comprises the cytochrome P450 protein family, which includes members involved in the synthesis of plant defence compounds. Genes encoding members of the GDSL-like lipase family (PF00657) were also upregulated in all pathosystems and are required for systemic ethylene-mediated resistance (Kim et al, 2013;Kwon et al, 2009).…”
Section: Similar Transcript Regulation In Selected Host-potyvirus Andmentioning
confidence: 99%